Thực trạng và biện pháp nâng cao chất lượng dạy học môn khoa học tự nhiên theo hướng trải nghiệm ở một số trường trung học cơ sở trên địa bàn thành phố Bắc Ninh - Nguyễn, Thị Thúy Hà; Hà, Lan Hương (Tạp chí Giáo dục, 2024)
Natural Science subjects according to the 2018 General Education program for secondary school students will be taught from the 2021-2022 school year, with the goal of forming and developing a scientific worldview in students, contributing to educating students to love nature, respect the laws of nature, and thereby know how to behave with nature in accordance with the requirements of sustainable social and environmental development. This article presents the current situation of teaching Natural Sciences in the direction of experience in some secondary schools in Bac Ninh city and proposes a number of appropriate measures to improve the quality of teaching Natural Sciences an experiential direction. The measures proposed in the article are urgent and highly feasible, serving as a direction to improve the quality of teaching Natural Sciences in an experiential direction for secondary school students in the study area.